Pheochromocytoma presenting as intra-cerebral hemorrhage in a young male - Basera, Pragati; Singh, Shivam; Siddiqui, Ammar S.; Anand, Aditya (International Journal of Research in Medical Sciences, 2022)
A male in his late teens presented with sudden onset left-sided hemiparesis and right-sided facial weakness. The patient had a history of persistent pulsatile headache for 1 year with the blurring of vision. He also had a history of diaphoresis and palpitations. The patient was diagnosed as a case of hypertension 1 year back. On examination, Right-sided upper motor neuron type facial palsy was present, and power was 0/5 in the left upper and lower limbs; BP was 220/120 mm Hg and was controlled using prazosin and nifedipine. A non-contrast computed-tomography scan (NCCT) of the brain revealed an intracerebral hemorrhage in the right ganglio-capsular region. Abdominal CT scan findings revealed a right suprarenal mass. 24-hour urinary normetanephrine was elevated, suggesting a diagnosis of pheochromocytoma. The surgical resection of the mass was delayed as the patient had developed Dengue shock syndrome, and he died of multiple organ dysfunction syndrome.